2021
DOI: 10.2174/1874613602115010001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Discriminatory Behavior Experienced by People Living with HIV in Indonesia: A Cross-sectional Study of the Demographic Health Survey

Abstract: Introduction: The discriminatory behavior experienced by People Living With HIV (PLWH) remains an unresolved problem in Indonesia. The aims of this research were to determine the factors associated with the discriminatory behavior experienced by PLWH in Indonesia. Methods: This study used cross-sectional design data by processing secondary data from the Indonesian Demographic Health Survey (IDHS) conducted in 2017. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…Several previous studies have shown that people living in urban areas were more intolerant of PLWH [ 44 46 ]. Moreover, people who live in rural areas and far from urban areas had a higher level of tolerance and kinship and were willing to accept living together with PLWH [ 23 , 37 , 47 , 48 ]. There was a lack of tolerance toward people with infectious diseases, thus encouraging stigmatization attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown that people living in urban areas were more intolerant of PLWH [ 44 46 ]. Moreover, people who live in rural areas and far from urban areas had a higher level of tolerance and kinship and were willing to accept living together with PLWH [ 23 , 37 , 47 , 48 ]. There was a lack of tolerance toward people with infectious diseases, thus encouraging stigmatization attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies in Indonesia on stigma toward PLWH have not shown a focus on youths. Previous studies have evaluated the determinants of stigmatization or discrimination but in respondents of all age levels [ 23 ], focused on PLWH’s parents [ 11 ], focused on youth respondents but did not describe the determinants of stigmatization attitudes [ 17 ], examined health care workers only [ 24 ], and only focused on ten regions [ 25 ]. In terms of measures to overcome stigma, around one-quarter of females did not give support for PLWH [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Late HIV diagnosis increases the risk of HIV transmission to others, as well as the chance of eventual illness and mortality and expensive health treatment [ 37 ]. Previous studies conducted in seven countries in the Asia–Pacific region, including Indonesia, revealed that the barriers to HIV testing were as follows: young age, engaged in sex work, transgender, injected drugs, perceived deficiency in health status, lack of insurance, fear of violation of confidentially, and self-referred for HIV testing [ 17 , 18 , 38 , 39 ]. However, several components were found to affect the prevalence of HIV testing in this study, including gender, wealth, region, stigma, and information related to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Although the HIV/AIDS has been existing for a long time, PLWH has shown better appearance due to the efficacy of anti-retroviral treatment (ART) (Narsai et al, 2016). Meanwhile, stigma and discrimination towards these people seemed not to have completely disappear due to many factors (Nursalam et al, 2021). A study examined HIV-related stigma among PLWH in rural central China and found that they suffered from the burden of HIV-related stigma at a moderate to high level (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%